Penerapan Sanksi Terhadap Pelanggar Peraturan Sekolah Di Madrasah Tsanawiyah - Zilhidayati Zilhidayati; Rengga Satria (An-Nuha, 2024)
This research was motivated by the lack of student discipline and the many violations of regulations in Madrasah Tsanawiyah Al-Ma'ruf Pasar Kambang. This research aims 1) To find out the forms of sanctions on rule violators at Madrasah Tsanawiyah Al-Ma'ruf Pasar Kambang 2) To find out the description of the implementation of sanctions in Madrasah Tsanawiyah Al-Ma'ruf Pasar Kambang 3) To find out the students' response to sanctions at Madrasah Tsanawiyah Al- Ma'ruf Pasar Kambang. This research uses descriptive qualitative research. The data sources in this study were students of class IX A and IX B of Madrasah Tsanawiyah Al- Ma'ruf Pasar Kambang. Data collection techniques in this study used participant observation.